STUDI EKPERIMENTAL UNJUK KERJA TURBIN ANGIN SUMBU HORISONTAL BERSUDU LOOPWING DAN PERANCANGAN SISTEM TRANSMISINYA - , JHON ARNOLDOS WABANG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wind turbine is a device that can be used to convert the kinetic energy in wind into mechanical energy and mechanical energy is converted into electrical energy via generator. Mechanism for utilization wind energy to generate electric power is a positive step because the energy is not polluting and environmentally friendly. Loopwing wind turbine with addition of a diffuser is one kind of wind turbine that is currently still in the research stage for increased efficiency due to blde shaped loop and have a sufficient number of blades to catch the wind kinetic energy that can be converted into mechanical energy and electrical energy. Loop-shaped blade design is very suitable for the area or areas that have the potential for low wind speed. This study was a laboratory scale in order to determine the performance of the wind turbine blade looopwing with addition diffuser and influence of wind speed variation on the torque and power generated as well as variations in the transmission gears are suitable for use in a DC generator that has a frequency of 500 rpm rotation and torque <0.2 Nm. Mechanisms of testing performed using 3 watt incandescent DC as a resistor and load measurement using a balance of weigh to determine the maximum torque and maximum power. From the experimental results, on the wind speed is 6.50 m / sec obtained maximum power and maximum torque of 0,09 Nm and 0,179W for transmission gear ratio,i=0,94